Simultaneous hydrogenation and acid-catalyzed conversion of the biomass-derived furans in solvents with distinct polarities - Hu, X.; Kadarwati, S.; Song, Y.; Li, Chun-Zhu (2016)
© The Royal Society of Chemistry 2016. Furfural and 5-hydroxymethylfurfural (HMF), the two typical biomass-derived furans, can be converted into biofuels and value-added chemicals via hydrogenation or acid catalysis or both. The potential competition between the hydrogenation and the catalyzed-conversion of HMF and furfural has been investigated with Pd/C and Amberlyst 70 as the catalysts at 170°C in various solvents. In water, the hydrogenation of HMF or the derivatives of HMF could take place, but the acid-catalyzed conversion of HMF to the diketones (2,5-hexanedione) was the dominant reaction pathway. On the contrary, with ethanol as the solvent, the full hydrogenation of HMF to 2,5-tetrahydrofurandimethanol was the dominant route, and the acid-catalyzed routes became insignificant. The efficiency for hydrogenation of HMF was much higher in ethanol than in water. As for furfural, its hydrogenation proceeded more efficiently in the polar solvents (i.e. ethanol, diethyl ether) than in non-polar solvents (i.e. toluene): a polar solvent tended to favor the hydrogenation of the furan ring in furfural over that of the carbonyl group in the same furfural.